Pengaruh Kompensasi dan Motivasi terhadap Kepuasan Kerja Karyawan pada PT Kranji Jaya Abadi - Fajri Alfa Febrian (Global Leadership Organizational Research in Management, 2024)
PT Kranji Jaya Abadi is a construction industry specializing in infrastructure development and large-scale commercial projects. This study aims to determine the effect of compensation and motivation on employee job satisfaction at PT Kranji Jaya Abadi. The research uses quantitative methods and data processing with SPSS 22. The population in this study consists of 32 respondents, with the sample being the entire population of 32 respondents. The sample was selected using a saturated sampling technique. Data were collected through observation and questionnaires involving 32 employees of PT Kranji Jaya Abadi. The results reveal that the compensation variable has a positive and significant effect on job satisfaction, with a T_count = 2.755 > T_table = 2.045 and a significance value of 0.010 < 0.05. Motivation has a positive and significant effect on job satisfaction, showing a T_count = 5.485 > T_table = 2.045 and a significance value of 0.00 < 0.05. The F test results show an F_count = 94.042 > F_table = 3.328 with a significance value of 0.00 < 0.05, indicating that compensation and motivation simultaneously have a positive and significant effect on job satisfaction. It is expected that the company maintains compensation and motivation to further enhance employee job satisfaction for the betterment of current and future employees.